About Study the Problems of Industrial Nature Use in the Lviv Region - Nazaruk, М. М.; Halianta, L . A. (Man and Environment. Issues of Neoecology, 2020)
Purpose. To determine the main directions of research, based on the analysis of the UA scientists’ works  devoted to the study of problems of industrial nature management, features of the development and functioning of various industries within the territory of the Lviv region.Results. Today, the transformation of the system of nature management goes beyond economic transformations and cannot ignore the previously described theories. Various issues of industrial nature use, its geospatial features in the region and the ecological problems caused by its development as well as features of their development and functioning within the territory of region allow to define the following basic directions of these researches: aspects of certain industries development, environmental and economic problems of industrial development.Conclusions. The powerful potential of nature management in the Lviv region can ensure the effectiveness of the transformations carried out in the region with a combination among economic, social and humanitarian spheres. The urgent tasks of the further development are as follows: to create an effective qualitatively advanced structure of the economy of the high-tech industrial complex of the developed social infrastructure as well as  to improve the ecological situation and living conditions of the population in the region.